Development of special endurance for cross-country skiers of 15-17 years old - Vysotskaya, T.; Golubnichy, S. (Journal of Human Sport & Exercise, 2021)
Purpose: to devise and prove experimentally a method of objective dosing of training exercises in the development of special endurance among young athletes in cross-country skiing. Materials and methods: the study involved cross-country skiers (15-17-year-old boys). The experiment took place on the basis of the Children's and Youth Sports School (Yakhroma, Russia). The experimental group used the special programs for the development of special endurance along with the generally accepted method. All microcycles in the one-year training cycle were divided into two types: containing special training exercises aimed at developing special endurance and not containing any, as a means of general physical training. Studies of the functional state of athletes were carried out using the diagnostic complex «Omega Standard». Results: the athletes of experimental group have significantly higher levels of special endurance. There was a distinct increase in results. Besides, the favourable changes of physiological parameters in the experimental group were proved such as: maximum oxygen consumption (ml/min/kg) from the beginning of the preparatory period to the end of this period increased by 2.8%, it was noted a significant slowing of the heart rate and an increase in stroke volume at rest. Conclusions: in the content of training exercises aimed at developing special endurance in the micro, meso and macrocycle training of cross-country skiers aged 15-17 yr., three variants of microcycles are identified (developing, supporting, restoring). The content of the first two may vary according to the predominant orientation of the training exercise on the basic factor (critical aerobic speed) and the main factors of special endurance (speed and stayer endurance).